2017
DOI: 10.1038/srep43375
|View full text |Cite
|
Sign up to set email alerts
|

Catch-and-Release of Target Cells Using Aptamer-Conjugated Electroactive Zwitterionic Oligopeptide SAM

Abstract: Nucleic acid aptamers possess attractive features such as specific molecular recognition, high-affinity binding, and rapid acquisition and replication, which could be feasible components for separating specific cells from other cell types. This study demonstrates that aptamers conjugated to an oligopeptide self-assembled monolayer (SAM) can be used to selectively trap human hepatic cancer cells from cell mixtures containing normal human hepatocytes or human fibroblasts. Molecular dynamics calculations have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Prevelex was synthesized as previously reported 34 and characterized using GPC and FT-IR spectroscopy to determine the molecular weight and functional groups. Subsequently, prevelex was dissolved in an aqueous ethanol solution and coated onto silicon substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevelex was synthesized as previously reported 34 and characterized using GPC and FT-IR spectroscopy to determine the molecular weight and functional groups. Subsequently, prevelex was dissolved in an aqueous ethanol solution and coated onto silicon substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Vapor deposition constitutes another approach for coating a surface with an ultrathin polymer layer. Surfaces modified with the aforementioned approaches considerably reduced protein adsorption and subsequent cell adhesion 34 , 35 . However, there are a few disadvantages to these approaches, such as complicated processes, use of toxic catalysts on the surface, and expensive equipment and materials.…”
Section: Introductionmentioning
confidence: 99%
“…The major interaction forces in the binding process are defined to be hydrogen bond and charge-charge interaction that are provided from native phosphodiester polymeric linker and the bases on loops. [27][28][29][30] The concept of aptamer ligands binding to proteins was reported early 1980s for the study of human immunodeficiency virus (HIV) and adenovirus. 31,32 In this investigation it had shown that the viruses have a high force of affinity and specificity for the encoding of small numbers of RNAs that bind to viruses or cellular proteins.…”
Section: Conventional Structurementioning
confidence: 99%